The MAKNA DAN DIMENSI KERUGIAN: ANALISIS TEMATIK PENAFSIRAN QS. AL-‘ASR : ANALISIS TEMATIK PENAFSIRAN QS. AL-‘ASR - Lindayati, Eka; Komarudin Sassi; Masykur Arif (Jurnal Studi Qur'an dan Tafsir, 2025)
Sometimes, verses of the Quran don't have a real impact on life because they are only read briefly. Therefore, it is necessary to carefully explore the meaning of the verses and chapters within it, including Surah Al-Asr. Surah Al-Asr is one of the most meaningful chapters in the Quran, serving as a significant reminder of the human condition—being in a state of loss, except for those who embody four essential qualities: faith, righteous deeds, enjoining truth, and enjoining patience. This study is a thematic (maudhū’i) interpretation that aims to deeply explore the meaning of QS. Al-‘Asr and reflect on its relevance to the current moral and social crises affecting the Muslim community. The research employs a qualitative approach through thematic exegesis, coupled with a sociological reflection on moral decline such as corruption, individualism, ethical degradation, and the erosion of social concern. The findings reveal that QS. Al-‘Asr offers a comprehensive solution to the multidimensional crises of the ummah, emphasizing the importance of true faith, beneficial actions, and a culture of mutual admonition as the foundation for collective reform. By adopting the values of QS. Al-‘Asr as guiding life principles, Muslims can rise from a state of loss toward a more meaningful and dignified existence.